The cultural landscape: From conservation to planning concept - Vasilјević Nevena (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2016)
The interpretation of the concept of cultural landscape, as well as the interpretation of the general concept of landscape, depends on the context in which the process takes place. As an antithesis to natural landscape, and as notion of spatial and temporal interaction of man and nature, the cultural landscape is conceptualized in terms of scientific approach. The experiences prove that the traditional dichotomy in defining the landscape value (natural vs. cultural), as well as the aspect of its protection, evolving into a holistic approach, which is promoted in European Landscape Convention, at the beginning of XXI century. In the modern theory and practice of spatial planning and nature protection, the concept of cultural landscape appears as a holistic, multidimensional and multifunctional entity, which, in times of globalization, should be preserved and developed in accordance with its regional and local identity (character). The question is: what kind of methodological approach should be applied in determining the landscape value in the spatial planning and nature conservation? The aim of the research is to explain the evolution of landscape approach form reductionism to holistic problem-oriented transdisciplinary research that allows appropriate evaluation of the cultural landscape potential and its application in the spatial planning concept. At the same time, the aim is to explain the conceptualization of the cultural landscape in terms of the institutional protection of natural and cultural heritage and spatial planning in Serbia. The purpose of this paper is to point to legal instruments of the Spatial Plan of the Republic of Serbia which defining the obligations of determining the landscape character in the planning concept in spatial and urban plans, as well as the re-evaluation of existing values of cultural landscapes. The subject of the paper is theoretical concept of cultural landscape and the character of the cultural landscape Tršić-Tronoša. The value of the landscape character is interpreted and metrically expressed for the purposes of the Study of protection of the landscape of exceptional features Tršić-Tronoša - cultural landscape. At the end, the finding of the presented research confirming the applicability of the methods of landscape characterization in the spatial planning concept.